The links between Louis Adamič and Slovene journalists and literary figures (1921-1941) - France Adamič (Dve Domovini, 1998)
The author discusses Louis Adamic’s contacts with some of the leading Slovene writers; he met most of them in person during his first visit to Slovenia in 1932. Among them were Josip Vidmar, Jus and Ferdo Kozak, Oton Zupančič, Ludvik Mrzel, Fran Albreht, Bratko Kreft, Anton Melik, Ludvik Klakočer and other literary figures and artists. He also met some translators, e.g. Griša Koritnik, Stanko Leben, Olga Škerl - Grahor andAnton Debeljak. In Bohinj he made the acquaintance of Fran Šaleški Finžgar, and inRogaška Slatina he established contacts with Ivan Hribar and France Kidrič, togetherwith his son Boris Kidrič. In Belgrade he met Minister Ivan Pucelj, the writer SlavkoSavinšek, the sculptor Lojze Dolinar and the publicist Tone Potokar. Adamič kept in touch with most of them until 1941. In 1949, when he visited his native land for a second time, he renewed the friendly acquaintances.